Optimization of dry reforming of methane over yttrium oxide-cobalt/mesoporous alumina using response surface methodology - M. S. A., Mohd Jailani; S. N., Miskan; M. B., Bahari; Herma Dina, Setiabudi (Elsevier Ltd, 2023)
Dry reforming of methane (DRM) has attracted significant attention due to its advantages in converting undesirable ozone-depleting gases, carbon dioxide (CO2) and methane (CH4), into syngas for Fischer-Tropsch synthesis. However, developing the best catalysts for DRM with superior catalytic activity and stability is still challenging. Additionally, process optimization is an important task for improving the efficiency, safety, and profitability of the process. Previously, our research group has reported an excellent catalytic performance of Yttrium Oxide-Cobalt/Mesoporous Alumina (Y2O3-Co/MA) due to the excellent distribution of Co and strong metal-support interaction. As a continuity, this study optimized the catalytic performance of Y2O3-Co/MA toward DRM. The optimization process was evaluated using the Response Surface Methodology (RSM) under three independent variables, which were reaction temperature (700 – 900 °C), weight hourly space velocity (15000–35000 mL gcat−1 hr-1), and CH4/CO2 ratio (1:1–3:1). The optimum operating conditions were successfully anticipated, with the good agreement of data between the model predictions and experiments. Y2O3-Co/MA presented the catalytic performance of XCH4 of 88.97%, XCO2 of 95.57%, H2 yield of 30.98%, and CO yield of 69.36%, at the reaction temperature of 900 °C, WHSV of 30,690 mL gcat-1h−1, and CH4/CO2 ratio of 1.027.